Risk appetites and empirical survival pattern of small and medium enterprises in Nigeria - Joshua S. Adeyele; Osazee G. Omorokunwa (The Journal of Entrepreneurial Finance (JEF), 2016)
Small and medium enterprises (SMEs) are vital to economic growth and development of a nation. However, many of them fail in the first five years of incorporation due to their exposures to risk financing and strategies employed to meet customers' need during business shutdown. Hence, this study is designed to verify how SMEs' risk financing affect their continuity, and to model their survival patterns in context of risk financing and risk management approach employed by the operators. Two hundred and nine copies of valid questionnaire distributed to the respondents were filled and returned. Cramer's V and multiple regressions were the statistical tools used for data analysis. Empirical failure and survival models were adopted for the selected SMEs. The findings revealed that: strong relationship exists between risk financing and business shutdown; there is a moderate but not significant relationship between risk financing and business continuity; and as efficient risk financing is employed, the SMEs' chance of survival also increased while the strategy employed to meet customers' need after business shutdown has inverse relationship with SMEs' survival. In light of these findings, recommendations on how to reduce SMEs' exposures to business shutdown and discontinuity were made.
Keywords: D81; L26; 650; insurable risk; SMEs' risk exposures; survival and failure; risk mitigation